The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/mnras/stab2653
|View full text |Cite
|
Sign up to set email alerts
|

How stars formed in warps settle into (and contaminate) thick discs

Abstract: In recent years star formation has been discovered in the Milky Way’s warp. These stars formed in the warp (warp stars) must eventually settle into the plane of the disc. We use an N-body+smooth particle hydrodynamics model of a warped galaxy to study how warp stars settle into the disc. By following warp stars in angular momentum space, we show that they first tilt to partially align with the main disc in a time scale of $\sim 1 {\:{\rm Gyr}}$. Then, once differential precession halts this process, they phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 83 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…8 Gyr for populations separated by stellar age, in four equally populated bins. The distributions are presented for stars formed in the main disc only, in order to a v oid warp stars that can take up to ∼6 Gyr to fully settle and phase mix into the disc (Khachaturyants et al 2021 ). Besides the o v erall m = 1 bend, we observe strong bending waves, in the z distributions (coherent red and blue structures).…”
Section: The Effect Of Stellar Agesmentioning
confidence: 93%
See 2 more Smart Citations
“…8 Gyr for populations separated by stellar age, in four equally populated bins. The distributions are presented for stars formed in the main disc only, in order to a v oid warp stars that can take up to ∼6 Gyr to fully settle and phase mix into the disc (Khachaturyants et al 2021 ). Besides the o v erall m = 1 bend, we observe strong bending waves, in the z distributions (coherent red and blue structures).…”
Section: The Effect Of Stellar Agesmentioning
confidence: 93%
“…The warped model has the same initial conditions as the simulation used in Khachaturyants et al ( 2021 ) and is produced via the method of Debattista et al ( 2015 ), which constructs triaxial dark matter models with gas angular momentum misaligned with the principal axes of the halo. showed that inserting rotating gas coronae within non-spherical dark matter haloes leads to a rapid and substantial loss of gas angular momentum.…”
Section: The Warped Model Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the outer part of the warp is also not described by a simple model-there are In addition, the morphology and kinematics of the warp depend on the type/age of the tracers (e.g., Romero-Gómez et al 2019;Chrobáková et al 2020). Moreover, hydrodynamic modeling of the evolution of an ensemble of stars formed in the warp shows that only younger populations trace the warp detected by HI (Khachaturyants et al 2021) and that the influence of the bending waves excited by irregular gas inflow is most strongly manifested in the young populations (Khachaturyants et al 2022). This means that the warp model, universal for all disk subsystems of the Galaxy, can hardly be accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the outskirts of the MW's disc seem to be both flaring (e.g., Amôres et al 2017;López-Corredoira et al 2018;Thomas et al 2018) and warping (e.g., Chen et al 2019;Yu et al 2021). Khachaturyants et al (2021) suggested that settled warp stars may contribute to the flaring of the youngest stellar populations observed at large galactocentric radii in the MW. In some cases, it could even be possible that the warps themselves might directly cause some vertical heating: bending waves, a phenomenon closely related to warping, have been proposed to heat discs (Khoperskov et al 2010;Griv 2011).…”
Section: Introductionmentioning
confidence: 99%